The relationship between HYDIN and fallopian tubal cilia loss in patients with epithelial ovarian cancer - Guo, Yuanli; He, Xinxin; Liu, Junfeng; Tan, Yanming; Zhang, Chao; Chen, Shan; Zhang, Sheng (Frontiers in Oncology, 2025)
IntroductionPrimary cilia play an important role in the development of cancer by regulating signaling pathways. Several studies have demonstrated that women with BRCA mutations have, on average, 50% fewer ciliated cells compared with general women. However, the role of tubal cilia loss in the development of epithelial ovarian cancer (EOC) remains unclear. Few specific studies have been found in linking HYDIN, a ciliary defect associated gene that encodes HYDIN axonemal central pair apparatus protein, which is involved in the transduction of Hedgehog (Hh) signal and is considered a cancer associated antigen, to ovarian cancer. Therefore, our study aimed to investigate the correlation between HYDIN gene mutations and tubal cilia loss in EOC.MethodsA whole exome sequencing (WES), immunohistochemistry (IHC), western blot, and reverse transcription quantitative (RT q) PCR were performed in 80 patients with EOC and 50 cases of non ovarian cancer to detect the mutations and expression of tubal ciliary marker, ciliary morphology, and abnormal rate.ResultsWe found that the incidence of tubal cilia loss was higher in EOC group with decreased expression of HYDIN compared with the control group (P<0.05).DiscussionThis study suggests that tubal ciliary loss is evident in epithelial fallopian tube carcinoma, and ciliary cells may be involved in the occurrence and development of EOC, and cilia-related gene HYDIN is expected to be a tumor marker for epithelial ovarian cancer.